Pemetaan Sistem Informasi Geografis Jumlah Kabupaten/Kota yang Mengalami Bencana Alam di Provinsi Jawa Tengah Tahun 2021 - Nilna Rusyda Widyaningsih; Bambang Agus Herlambang; Ahmad Khoirul Anam (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
Natural disasters have become the focus of global attention because of their widespread and often destructive impacts. In national strategic planning, BNPB Head Regulation No. 2 of 2012 regarding disaster risk management is stated, which states that disaster vulnerability mapping is important for disaster mitigation strategies. This research produces maps and classifications of vulnerabilities in districts/cities in Central Java. Web-based Geographic Information System with case studies on the number of districts/cities experiencing natural disasters in Central Java Province in 2021 aims to provide information to users regarding disaster location points. This is intended so that people who want to know areas prone to natural disasters and avoid these locations can easily use it. With this application, it is hoped that it can be used to obtain information on the location of natural disasters in Central Java Province in 2021.